Hypoxia Promotes Resistance to EGFR Inhibition in NSCLC Cells via the Histone Demethylases, LSD1 and PLU-1 - Lu, Yuhong; Liu, Yanfeng; Oeck, Sebastian; Glazer, Peter M. (Molecular cancer research, 2018)
The development of small-molecule tyrosine kinase inhibitors (TKI) specific for epidermal growth factor receptors (EGFR) with activating mutations has led to a new paradigm in the treatment of non–small cell lung cancer (NSCLC) patients. However, most patients eventually develop resistance. Hypoxia is a key microenvironmental stress in solid tumors that is associated with poor prognosis due, in part, to acquired resistance to conventional therapy. This study documents that long-term, moderate hypoxia promotes resistance to the EGFR TKI, gefitinib, in the NSCLC cell line HCC827, which harbors an activating EGFR mutation. Following hypoxic growth conditions, HCC827 cells treated with gefitinib upregulated N-cadherin, fibronectin, and vimentin expression and downregulated E-cadherin, characteristic of an epithelial-mesenchymal transition (EMT), which prior studies have linked to EGFR TKI resistance. Mechanistically, knockdown of the histone demethylases, LSD1 and PLU-1, prevented and reversed hypoxia-induced gefitinib resistance, with inhibition of the associated EMT, suggesting that LSD1 and PLU-1 play key roles in hypoxia-induced gefitinib resistance and EMT. Moreover, hypoxia-treated HCC827 cells demonstrated more aggressive tumor growth in vivo compared with cells grown in normoxia, but inhibition of LSD1 function by shRNA-mediated knockdown or by the small-molecular inhibitor SP2509 suppressed tumor growth and enhanced gefitinib response in vivo. These results suggest that hypoxia is a driving force for acquired resistance to EGFR TKIs through epigenetic change and coordination of EMT in NSCLC. This study suggests that combination of therapy with EGFR TKIs and LSD1 inhibitors may offer an attractive therapeutic strategy for NSCLCs. Mol Cancer Res; 16(10); 1458–69. ©2018 AACR.